Temperature Sensing Diode in InP-Based Photonic Integration Technology - Wenjing Tian; Bart Bas; Dylan Harmsen; Kevin Williams; Xaveer Leijtens (IEEE Photonics Journal, 2024)
The integration of temperature sensors directly onto photonic platforms facilitates the thermal management of advanced photonic integrated circuits. This paper presents monolithic temperature sensors on the indium-phosphide-based photonic integration technology. Two distinct sensors were developed using p-i-n diode junctions with different waveguide core layers, one composed of multiple quantum wells and the other of bulk indium gallium arsenide phosphide. Introducing these sensors to an indium-phosphide-based generic foundry platform required zero process modifications. Theoretical, simulation, and measurement results consistently reveal a linear relationship between the forward voltage of the sensors and temperature under constant current biasing. The measurement results highlight that the compact sensors with dimensions of 30 × 10 $μ$ m achieve the highest sensitivity of $-$ 2.1 mV/K. These sensors boast a simple structure, easy operation, straightforward temperature interpretation, and high compatibility with the foundry process. They present immunity to on-chip (stray) light, a critical feature when operating alongside integrated lasers. The results demonstrate the feasibility of local temperature measurement and monitoring of photonic integrated circuits.